The Effect of Training and Organizational Culture on Employee Performance Mediated by Work Discipline in the Electronic Facility & IT Division PT. Angkasa Pura II (Persero) Kantor Cabang Bandara Internasional Kualanamu - Hazmanan Khair (Jurnal Mantik, 2022)
The purpose of this study was to determine and analyze the effect of training and organizational culture on employee performance mediated by work discipline in the Electronic Facility & IT division of PT Angkasa Pura II (Persero) Kualanamu International Airport. The sample in this study used a saturated sample, where all of the population was sampled. The sample in this study amounted to 35 employees. The data collection technique in this study used the questionnaire method, while the data analysis technique in this study used a quantitative approach, with SEM-PLS statistical analysis. Data processing in this study using the software program SmartPLS 3.3.3. The results of this study prove that directly training has a positive but not significant effect on employee performance, directly organizational culture has a negative and insignificant effect on employee performance, direct work discipline has a positive and significant effect on performance, and direct training has a positive and significant effect on discipline. work, directly organizational culture has a positive and significant effect on work discipline, indirectly training has a positive and significant effect on employee performance mediated by work discipline, indirectly organizational culture has a positive but not significant effect on employee performance mediated by work discipline. This shows that work discipline mediates the effect of training on performance and work discipline mediates the influence of organizational culture on performance in the Electronic Facility & IT division of PT Angkasa Pura II (Persero) Kualanamu International Airport.